Comparative study of accompaniment programs for undergraduate degree students in Spanish universities - García-Cardo, Susana; Queiruga-Dios, Marián; Queiruga-Dios, Araceli (Frontiers in Psychology, 2023)
In the last decade, higher education has undergone a transformation in different areas. The most recent and impactful one may have been the need to keep it updated during the COVID-19 pandemic and to be able to teach remotely and affect the university life as little as possible. Another significant change is the personal attention, accompaniment, or mentoring programs that has become the leitmotiv in many universities. Therefore, this study was developed to compare the different programs from the 60 Spanish universities. The relevant information collected during this research is related to the existence of an accompaniment program; and in this program, who plays the role of mentor that can be a teacher, an alumni, or a student in the last year of the degree. Sometimes, the program is focus on first-year students, or students from all years, or students attending specific courses, or incoming students as part of a university exchange, graduates, or postgraduates. Other information collected from the search is related to the type of mentoring program, whether or not there is a regulated or formal program and, therefore, it depends on whether or not it is linked to a course. Moreover, the assessment procedures are also indicated, in case any evaluation is used. Apart from the analysis developed during this research, the mentor-mentee program implemented at the Francisco de Vitoria University is detailed, highlighting differences from other programs, its advantages and students benefits.